If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (N + 7)(8n + 3) = 0 Reorder the terms: (7 + N)(8n + 3) = 0 Reorder the terms: (7 + N)(3 + 8n) = 0 Multiply (7 + N) * (3 + 8n) (7(3 + 8n) + N(3 + 8n)) = 0 ((3 * 7 + 8n * 7) + N(3 + 8n)) = 0 ((21 + 56n) + N(3 + 8n)) = 0 (21 + 56n + (3 * N + 8n * N)) = 0 (21 + 56n + (3N + 8nN)) = 0 Reorder the terms: (21 + 3N + 56n + 8nN) = 0 (21 + 3N + 56n + 8nN) = 0 Solving 21 + 3N + 56n + 8nN = 0 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + 3N + 56n + -21 + 8nN = 0 + -21 Reorder the terms: 21 + -21 + 3N + 56n + 8nN = 0 + -21 Combine like terms: 21 + -21 = 0 0 + 3N + 56n + 8nN = 0 + -21 3N + 56n + 8nN = 0 + -21 Combine like terms: 0 + -21 = -21 3N + 56n + 8nN = -21 Add '-56n' to each side of the equation. 3N + 56n + -56n + 8nN = -21 + -56n Combine like terms: 56n + -56n = 0 3N + 0 + 8nN = -21 + -56n 3N + 8nN = -21 + -56n Reorder the terms: 21 + 3N + 56n + 8nN = -21 + -56n + 21 + 56n Reorder the terms: 21 + 3N + 56n + 8nN = -21 + 21 + -56n + 56n Combine like terms: -21 + 21 = 0 21 + 3N + 56n + 8nN = 0 + -56n + 56n 21 + 3N + 56n + 8nN = -56n + 56n Combine like terms: -56n + 56n = 0 21 + 3N + 56n + 8nN = 0 The solution to this equation could not be determined.
| 12y=18+6y | | -6x--2x+4=-6 | | 3x^4+5x^3-3x+42=0 | | 5×3/10 | | log(5x^4y^10/z^10) | | -31x+248=0 | | 144x-48=96x+8 | | ((3x-5)/(x^2-9))1 | | 144x-48=96+8 | | 3/5p+4=6/5p-8 | | 8+3x(a-5)=-28 | | x-95=25 | | 3r+200=2r+1000 | | 2s^2-7-15=0 | | .25(x+2)=27 | | 8x-9y=-1 | | -15c+8c+6c=-15 | | 8-12m=6*(1+m) | | -d+20=-6d+16d-2 | | 58218374929284729x-42928=0 | | x+21+147=147 | | R/6=10/9 | | 7y(6y+3)=12 | | 12-1a=45 | | 2/1088= | | -6a+4+3a=-23 | | 3+2m=m+3-8 | | 20x+10y=3000 | | 25-(4-6x)=9-(7x-2) | | y=-17sin(10t-1) | | ln(8)-ln-4(x)=1 | | 5(r+2)7r= |